Empowering Rural Communities Through Waste Bank Socialization for Sustainable Environmental Management - Nuriyatman, Eko; Mushawirya, Rustian; Syam, Fauzi; Kurnia Putra, Akbar; Fauzani Raharja, Ivan (LPPM Universitas Jambi, 2023)
This community service initiative aimed to increase environmental awareness among residents of Pelayang Raya Village, Indonesia, through a socialization program focused on the establishment of a community-based waste bank. The activity involved 60 participants, including village officials, women’s groups, youth organizations, and traditional leaders. The program introduced key concepts of waste management based on the 3R principles—reduce, reuse, and recycle—while also outlining the operational mechanisms for forming and managing a waste bank. As a result, participants reached a consensus to formally establish a waste bank and agreed to follow up with student-assisted implementation through the MBKM KKN-T program. The project succeeded in fostering collaboration between community stakeholders, raising awareness, and laying a foundation for sustainable waste governance. However, the initiative was limited by its one-time implementation, uneven community participation, and the absence of a formal legal framework. Future programs should include ongoing training, regulatory support, and strategies for waste valorization to maximize the impact. Overall, the activity demonstrated the potential of participatory, community-driven environmental initiatives to build sustainable local systems and support rural circular economy models.